Studi Mikrobiologis terhadap Jenis Bakteri yang Terlibat dalam Proses Fermentasi Tempoyak Buah Durian - Nazwa Nayla Putri; Ardi Mustakim (International Forum of Researchers and Lecturers, 2025)
Tempoyak is a traditional Indonesian fermented food made from the flesh of durian (Durio zibethinus Murr.), which undergoes spontaneous fermentation driven by indigenous microorganisms. The fermentation process generally occurs under anaerobic conditions and is primarily dominated by lactic acid bacteria (LAB), including species such as Lactobacillus, Leuconostoc, and Pediococcus. These bacteria play a crucial role in modifying the physicochemical properties of the product, including a significant reduction in pH, an increase in the concentration of organic acids, and the formation of volatile compounds responsible for tempoyak’s distinctive aroma and overall flavor complexity. In addition to enhancing its unique sensory profile, the fermentation process also extends the shelf life and introduces probiotic potential to the final product. This study aims to observe and analyze the microbiological and chemical aspects of tempoyak fermentation and to evaluate its potential as a local functional food with health-promoting properties. Laboratory tests and microbial analyses confirmed that the fermentation process not only retains essential nutrients but also promotes the growth of beneficial bacteria, provided the production conditions are hygienically maintained at all stages. The study emphasizes the importance of controlled fermentation techniques to ensure product safety and consistent quality. Furthermore, the findings reveal that tempoyak could serve as a promising probiotic-rich food that supports digestive health, contributing to the diversification of traditional Indonesian fermented foods. With its appealing flavor, cultural value, growing consumer interest, and potential health benefits, tempoyak holds significant promise for future development and commercialization, particularly in the field of functional food innovation rooted in indigenous culinary practices.